2015
DOI: 10.5194/acp-15-13453-2015
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the spectral dependence of linear particle depolarization ratio of aerosols using NASA Langley airborne High Spectral Resolution Lidar

Abstract: Abstract. Linear particle depolarization ratio is presented for three case studies from the NASA Langley airborne High Spectral Resolution Lidar-2 (HSRL-2). Particle depolarization ratio from lidar is an indicator of non-spherical particles and is sensitive to the fraction of non-spherical particles and their size. The HSRL-2 instrument measures depolarization at three wavelengths: 355, 532, and 1064 nm. The three measurement cases presented here include two cases of dust-dominated aerosol and one case of smok… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
266
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(285 citation statements)
references
References 63 publications
(102 reference statements)
18
266
0
1
Order By: Relevance
“…The numerous field observations indicate that the total dust linear depolarization ratio is always around 0.3 at 532 nm (close to the dust sources as well as after long-range transport). In contrast, the 1064 nm dust depolarization ratio was found to vary strongly from values of 0.22 to 0.28 for lofted dust layers (and typical dust size distribution after regional as well as long-distance travel; Freudenthaler et al, 2009;Burton et al, 2015;Haarig et al, 2017a) to values around 0.4 (Burton et al, 2015) close to dust sources. Only during events close to dust emission zones when giant dust parti-3406 R.-E. Mamouri and A. Ansmann: Fine and coarse dust profiling cles and even sand particles (having diameters > 60 µm) are in the air, such very high particle linear depolarization ratios are obviously measurable at 1064 nm.…”
Section: Field Observationsmentioning
confidence: 89%
See 2 more Smart Citations
“…The numerous field observations indicate that the total dust linear depolarization ratio is always around 0.3 at 532 nm (close to the dust sources as well as after long-range transport). In contrast, the 1064 nm dust depolarization ratio was found to vary strongly from values of 0.22 to 0.28 for lofted dust layers (and typical dust size distribution after regional as well as long-distance travel; Freudenthaler et al, 2009;Burton et al, 2015;Haarig et al, 2017a) to values around 0.4 (Burton et al, 2015) close to dust sources. Only during events close to dust emission zones when giant dust parti-3406 R.-E. Mamouri and A. Ansmann: Fine and coarse dust profiling cles and even sand particles (having diameters > 60 µm) are in the air, such very high particle linear depolarization ratios are obviously measurable at 1064 nm.…”
Section: Field Observationsmentioning
confidence: 89%
“…These values are mostly derived by combining the laboratory studies (of the fine dust depolarization ratios) and a variety of field observations of the total (fine + coarse) dust depolarization ratio. Burton et al (2015) reported high particle linear depolarization ratios around 0.4 for 532 and 1064 nm, as found by Sakai et al (2010), in dense dust plumes over the United States close to the ground and probably close to the dust sources with a strongly dominating coarse mode. Veselovskii et al (2016) and Hofer et al (2017) found maximum particle depolarization ratios around 0.35 at 532 nm, respectively, in dense western African and central Asian dust plumes.…”
Section: Field Observationsmentioning
confidence: 90%
See 1 more Smart Citation
“…We implemented new channels to permit simultaneous observations of dust linear depolarization ratios at 355, 532, and 1064 nm. Freudenthaler et al (2009) and Burton et al (2015) showed already that the dust linear depolarization ratio significantly changes with the transmitted laser wavelength, obviously as a result of changing contributions of fine-mode dust particles (particles with diameters < 1 µm) and coarse-mode (super-micrometer) particles to the light depolarization. Burton et al (2015) recently presented triplewavelength polarization lidar observations in an aged and fresh dust layer performed with an airborne high-spectralresolution lidar (HSRL-2).…”
mentioning
confidence: 99%
“…Freudenthaler et al (2009) and Burton et al (2015) showed already that the dust linear depolarization ratio significantly changes with the transmitted laser wavelength, obviously as a result of changing contributions of fine-mode dust particles (particles with diameters < 1 µm) and coarse-mode (super-micrometer) particles to the light depolarization. Burton et al (2015) recently presented triplewavelength polarization lidar observations in an aged and fresh dust layer performed with an airborne high-spectralresolution lidar (HSRL-2). The main goal of the paper is to present for the first time ground-based triple-wavelength polarization/Raman lidar observations (case studies) of the depolarization ratio of Saharan dust after long-range transport and to provide a high-quality statistical data set of dust depolarization ratios at 355, 532, and 1064 nm.…”
mentioning
confidence: 99%